Mitigating Slope and Embankment Erosion in Malaysia: Case Studies and Integrated Approaches - Siti Farhanah S.M Johan; Abang Nur’Iman Aiman Abang Mohamad Najib; Chan Chee Ming; Sarani, Noor Amira; Noorhayatie Yusof (International Journal of Integrated Engineering, 2026)
Malaysia faces severe slope and embankment erosion, a critical geohazard driven by heavy rainfall, intense tropical weathering, and poorly planned development. This results in significant economic and human losses, with failures largely attributed to human factors in design, construction, and maintenance. Current mitigation employs conventional methods such as gabions for immediate stability and soft or bioengineering for ecological control. While integrated approaches are crucial, they face challenges in long-term performance, maintenance, and addressing systematic human errors, which contribute to 57% of landslides, 29% of structure or design factors and 14% of geological factors. This paper critically analyzes integrated solutions in Malaysia, focusing on their long-term efficacy and capacity to mitigate human-induced vulnerabilities, aiming to provide actionable insights for resilient and sustainable erosion control.